Two Case Studies in Predictable Application Scheduling Using Rialto/NT - Jones, Mike; Regehr, John; Saroiu, Stefan (Appeared in Proceedings of the Seventh Real-Time Technology and Applications Symposium (RTAS 2001), 2001)
This paper analyzes the results of two case studies in applying the Rialto/NT scheduler to real Windows 2000 applications. The first study is of a soft modem—a modem whose signal processing work is performed on the host CPU, rather than on a dedicated signal processing chip. The second is of an audio player application. Both of these are frequently used real-time applications—ones running on systems that were not designed to support predictable real-time execution. To function correctly, both applications require that ongoing computations be performed in a timely manner. In both cases, we first measured an original version designed to run on Windows 2000, and then modified the application to take advantage of ongoing CPU Reservations provided by the Rialto/NT scheduler. We report on the benefits and problems observed when using reservations in these realworld scenarios. In both cases, we found that a real-time scheduler can provide the needed predictability for the application in the presence of competing applications, while also providing other benefits, such as minimizing the soft modem’s impact on the scheduling predictability of other computations in the system. We also describe the methodologies we used to analyze the real-time behavior of the operating system and applications during these studies, including the use of instrumented kernels to produce execution traces.